Determination of polyphenol oxidase and peroxidase activity in plants rich in phenolics and chlorophylls - Sommano , Sarana R (Journal of Postharvest Technology, 2018)
Investigating the enzyme activities involved in the browning of plant tissues can be difficult when there are high amounts of endogenous phenols and / or there is a ‘latent stage’ (viz., membrane bound) of the browning enzymes polyphenol oxidases (PPOs) and peroxidases (PODs) in the crude extract. To extract or partial purify of these enzymes involves removal of phenolic metabolites and activation of the enzyme from its latent stage. The highly reactive phenolic compounds can be removed by incorporating polyvinylpyrrolidone (PVP) or polyvinylpolypyrrolidone (PVPP) and polyethylene glycol (PEG) into enzyme extraction solutions, thus improving enzymatic activity. PPO are present naturally in latent forms, and thus extraction of these enzymes may require the use of activation agents such as sodium dodecyl sulphate (SDS) and detergents such as Triton X (TTX). However, these detergents have disadvantages in that they also release chlorophylls, which give a dark green supernatant and later interfere with enzymatic activity. To overcome this problem, extraction of the enzymes using temperature-induced phase separation in TTX 114 was introduced. Within this review, the detailed overview of the current phytochemical approaches for extraction and purification of such enzymes are described.